2019
DOI: 10.15244/pjoes/99064
|View full text |Cite
|
Sign up to set email alerts
|

Host Specificity, Community Components and Diversity Dynamics of Dactylogyrus spp. (Monogenean ectoparasites) Parasitizing Cyprinid Gills

Abstract: Habitually, gills of cyprinid fish have deemed the natural habitats of Dactylogyrus spp. worldwide. Taxonomically, this common monogenean ectoparasite belongs to the Dactylogyridae family. It could be mentioned that the current study is the first comprehensive attempt at highlighting the host specificity of this flatworm parasite that affects Iraqi freshwater fish. Moreover, community components of the parasite and diversity dynamics are also elaborated upon. A total of 681 fish belonging to 18 species (Cyprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Moreover, this may also imply that endemic hosts are under-explored and, therefore, that the host range of some endemic Dactylogyrus species may be wider than is actually documented, similarly as for D. omenti. This species was recently considered as a specialist of A. huegelii in the Balkans [ 31 ]; however, Koyee and Abdullah [ 62 ] reported D. omenti also from Middle Eastern L. xanthopterus. The validity of D. omenti was in their study also supported by the molecular data.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this may also imply that endemic hosts are under-explored and, therefore, that the host range of some endemic Dactylogyrus species may be wider than is actually documented, similarly as for D. omenti. This species was recently considered as a specialist of A. huegelii in the Balkans [ 31 ]; however, Koyee and Abdullah [ 62 ] reported D. omenti also from Middle Eastern L. xanthopterus. The validity of D. omenti was in their study also supported by the molecular data.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the tree surface similarities derived from the phylogenetic analysis, carried out by Chiary et al (2014), have revealed that D. mascomai and D. lenkoranoides are genetically closely associated sister species and a high value of bootstrap was obtained for the branch formed by these sibling species. Although the current investigation has encompassed two aspects (DNA-based sequence and morphological features), only the DNA--based was depended in this study, whereas Dactylogyrids morphology-based diversification was reported in another study (Koyee and Abdullah 2019). In this regard, certain studies have pointed out that at least three characters are required to entail 95% bootstrap support, but non-contradicted groups boosted by less than three characters will essentially receive less than 95% support.…”
Section: Discussionmentioning
confidence: 74%
“…However, no previous study focusing on the diversity of monogeneans parasitizing fish species in Iraq applied genetic data for taxonomical purposes, nor performed molecular phylogenetic reconstruction. Besides the studies of Koyee and Abdullah (2019) and Benovics et al . (2021 a ), no genetic data are so far available for Iraq monogeneans.…”
Section: Introductionmentioning
confidence: 86%
“…However, no previous study focusing on the diversity of monogeneans parasitizing fish species in Iraq applied genetic data for taxonomical purposes, nor performed molecular phylogenetic reconstruction. Besides the studies of Koyee and Abdullah (2019) and Benovics et al (2021a), no genetic data are so far available for Iraq monogeneans. Recently, an integrative approach combining genetic characterization with commonly used, taxonomically important morphological characters has become the gold standard with respect to taxonomical research on monogeneans (e.g.…”
Section: Introductionmentioning
confidence: 99%